FEEDING DIFFERENT TYPES OF FEED ON VANNAMEI SHRIMP (LITOPENAEUS VANNAMEI) MAINTAINING WITH LOW SALINITY MEDIA (Jurnal Media Akuakultur Indonesia, 2022)
This study aims to determine the effect of giving different types of feed to the value of Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), and Survival (SR) vannamei shrimp (Litopenaenus vannamei) in the maintenance of media with 2 ppt salinity. The research method used is an experimental method using a Completely Randomized Design (CRD) consisting of 3 treatments and each repeated 4 times. The first (P1), second (P2), and third (P3) treatments were rearing vannamei shrimp with pelleted feed, natural feed for silk worms (Tubifex tubifex), and a combination of the two. The results showed that the provision of different types of feed gave a significant effect on the value of the Specific Growth Rate (SGR) of vannamei shrimp. Feeding a combination of silk worms (Tubifex tubifex) and pelleted feed was the best treatment with an SGR value of 6.07% BW/day. The treatment given in this study did not have a significant effect on the FCR and SR values. The results of observations of water quality during this study included the value of the degree of acidity (pH) which ranged from 6.6 to 6.8, then the temperature ranged from 24.3 -24.5 oC, the salinity was homogeneous, which was 2 ppt, and dissolved oxygen (DO) which ranged from 6.8 to 7.3 mg/l.
Keywords: Pakan; Udang vannamei; Litopenaeus vannamei; Laju Pertumbuhan Spesifik (SGR); Rasio Konversi Pakan (FCR); Sintasan (SR)